Pengaruh Abu Ketel sebagai Bahan Penambah Campuran Beton Normal terhadap Kuat Tekan - Hidayatullah, Hadi; Irianti, Laksmi; Helmi, Masdar; Widyawati, Ratna (Universitas Lampung, 2024)
Much of the kettle ash waste found in palm oil mills is wasted and can pollute the environment. Therefore, efforts need to be made to handle this waste. One of them is its use as an additional ingredient in concrete mixtures. . This research aims to analyze the effect of kettle ash on the rate of increase in compressive strength through laboratory testing with variations in kettle ash used, namely 0%, 5%, 10%, 15% and 20% of the cement weight. The test specimens have dimensions of 15 cm x 15 cm x 15 cm with testing times at 3 days, 7 days, 14 days, 28 days and 56 days. Based on analysis of research data, it was found that the majority experienced an increase in the compressive strength of concrete without additional materials. Increases occurred at 3 days, 7 days, 14 days and 28 days. The percentage increase in compressive strength for the majority decreased at the age of 3 days, 7 days, 14 days. Meanwhile, at the age of 56 days the majority experienced an increase in the percentage of compressive strength which was caused by a quite significant increase in compressive strength. The highest compressive strength at 56 days was produced by test object code BAK 1 of 38.59 MPa